MENINGKATKAN KEMAMPUAN SISWA PADA ASPEK BERPIKIR KREATIF MATEMATIKA MELALUI PEMBELAJARAN PROBLEM POSING - Diyanah, Mahirah; Firdausi, Yusrotin Noor (Jurnal Pembelajaran Matematika, 2018)
Abstract: Low creative thinking ability can result in low mathematics problem solving ability. In achieving creative thinking indicator, students are required to carry out creative activities, such as answering mathematics tasks continuously. In relation with this condition, a supportive learning model is needed to improve students' ability in the aspect of creative thinking. One of learning models that can be applied in improving students' creative thinking ability is problem posing. In Problem Posing, students are asked to make questions based on information or situations given through group discussion activities. This study aims to determine whether there are differences in students’ creative thinking ability before being taught with Problem Posing learning and after being taught with it. It is also intended to determine whether there is an increase in students' creative thinking ability through the implementation of Problem Posing. The sample of this study is students of VII E of State Junior High School (SMPN) 1 Karanganyar. This is experimental research which applies One-Group Pretest-Posttest Design. Data analysis is performed at the pretest and posttest values using t test and n-gain test. The results show that there is an increase in students’ creative thinking ability up to 0.32, which included as medium improvement.Keywords:Creative Thinking, Problem Posing.